A preclinical rodent model of radiation induced lung injury for medical countermeasure screening in accordance with the FDA animal rule - Jackson, Isabel L. (2012)
The purpose of pre-clinical murine model development is to establish that the pathophysiological outcome of our rodent model of radiation-induced lung injury is sufficiently representative of the anticipated pulmonary response in the human population. This objective is based on concerns that the C57BL/6J strain may not be the most appropriate preclinical model of lethal radiation lung injury in humans. In this study, we assessed this issue by evaluating the relationship between morbidity (pulmonary function, histopathologic damage) and mortality among three strains of mice, C57BL/6J, CBA/J, and C57L/J. These different strains display variations in latency and phenotypic expression of radiation-induced lung damage. By comparing the response of each strain to the human pulmonary response, we established an appropriate animal model(s) of human radiation-induced pulmonary injury. Observations in the C57L/J and CBA/J murine models can be extrapolated to the human lung for evaluation of mechanisms of action of radiation as well as future efficacy testing and approving agents that fall under the “Animal Rule” of the US Food and Drug Administration (FDA) (21 CFR Parts 314 and 601).